A dynamic charging strategy with hybrid fast charging station for electric vehicles. (1st July 2020) - Elma, Onur
Abstract: The popularity of electric vehicles (EV) have been on the rise with technological advancements and environmental concerns. The charging time and charging demand are important challenges for EV adaptation. In order to address these challenges, a DC fast charging technology with a dynamic energy management system is proposed in this study. However, DC fast chargers require high power demand periods to reduce the charging time. This, in turn, will cause negative effects on the grid such as stability, resilience, and efficiency problems. The purpose of the study is to evaluate a hybrid DC fast charging station with the aim of reducing peak demand during charging periods. The proposed energy management algorithm together with the dynamic data use provides more reliable results on such systems operations. With the proposed control algorithm, both peak demand from the grid is substantially reduced by 45% and the battery life span is extended thanks to more controlled charge/discharge coordination. Highlights: Energy management algorithm is proposed to reduce fast-charging demand on the grid. The hybrid energy structure in the fast-charging system is introduced. The aim is to minimize peak demand on the grid side. The performance of the proposed system has been validated with case studies. The fast-charging system can be more widespread with the proposed system.